Pengaruh Media Interaktif Berbasis AI Terhadap Literasi Membaca dan Kemampuan Berargumen Logis Murid Sekolah Dasar - Rebin Bima Septian; Hena Dian Ayu; Atna Tiningrum (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This study aims to describe the improvement of students’ reading literacy and logical argumentation skills through the implementation of interactive media based on Artificial Intelligence (AI). The study employed a descriptive qualitative method using the Classroom Action Research (CAR) approach based on the Kemmis and McTaggart model, which includes the stages of planning, action, observation, and reflection. The research was conducted in the fifth grade of SDN Pisang Candi 3 Malang involving 11 students, consisting of 6 female students and 5 male students. The research instruments included tests, observation sheets, documentation, and field notes. Data validity was ensured through source and technique triangulation. The results showed an improvement in students’ reading literacy and logical argumentation skills. Quantitatively, learning mastery increased from 45.45% in the pre-cycle with an average score of 70.82 to 72.73% in Cycle I with an average score of 78.55, and reached 90.91% in Cycle II with an average score of 87.5. Qualitatively, students became more active, confident, and able to express opinions logically during the learning process. The study concludes that AI-based interactive media are effective in improving elementary school students’ reading literacy and logical argumentation skills. This research has implications for the development of interactive, innovative, and student-centered digital learning.